Lived Experiences of Non-Indigenous Teachers in an Aeta Community: A Phenomenological Study - Orcales-Tabile, Delyn (Future Science / FSH-PH Publications, 2024)
This study aimed to determine the experiences of non-indigenous teachers assigned in an IP school. Learning and respecting the cultural protocols in gaining the trust not only for their students but also for the whole Aeta community to become an effective teacher of the diverse learners. Understanding how non-indigenous teachers and indigenous teachers work together to provide quality education that both meet its standards while maintaining their rich cultural heritage. The researcher utilized a phenomenological research study followed a transcendental approach to explore the experiences of non-indigenous teachers assigned in an IP community for the school year 2019-2020. The participants of the study were the six female and two male non-indigenous teachers designated in an IP community for a year or more. Eight participants are senior and junior high school teachers and one master teacher at LAKAS high school. Total population sampling is used to yield data for this study. Since the number of non-IP teachers assigned in LAKAS high school is very small. Based on the gathered data, there are 7 themes emerged in this study that described the qualities of non-IP teachers. The following themes are (1) cognizant, (2) self-fulfilling, (3) adaptable, (4) collaborative (5) and compassionate.